A Traditional and Non-traditional Export Performance Assessment: An empirical examination of factors enhancing the competitiveness of Zambia's Exports - Nsakaza, Kalimanshi; Kanchebele, Emmanuel (International Journal of Economics and Management, 2024)
This study examined the performance of traditional and non-traditional exports and further analyzed the factors that determine their performance in Zambia using a time series analysis (1960 and 2021). With the aid of the Vector error correction model, the study found that increases in the Real GDP, and Foreign Direct Investment of Zambia positively and significantly affected the volume of exports. In the analysis of aggregate exports, the non-significance of the relative price elasticity (Foreign Exchange rate) suggests that trade policies that concentrate overly on expenditure switching such as tariff and non-tariff restrictions or devaluations do not effectively assist trade policy reform efforts. The study thus recommends the need to promote inclusiveness, diversification and growth in investment towards the production of export commodities, particularly through the Multi-Facility Economic Zones by providing incentives to expand export diversification and growth at the local level through revising the Fiscal and non-Fiscal incentive thresholds in MFEZs to reflect the financing capacity of local investors.